Transposição didática da computação quântica: - Silva, João Marcos Costa da (2023)
In this paper, we propose the development of a white paper to help students learn about and manipulate quantum information using mathematical tools in a high school context. We present an analysis of the teaching of Modern and Contemporary Physics (MCP) in Brazil and its absence in the curriculum proposed for high school. We discuss the theory of quantum computing, in particular about logic gates and quantum circuits, with the related mathematical and conceptual apparatus. We apply three active methods Learning by Doing, Teaching and Learning Sequence, and Problem-Based Learning. In this way, we have combined Modern and Contemporary Physics content with active methods and developed a pedagogical product that has been used with high school students. Also, we discuss the application of the teaching tool with the proposed peda- gogical proposal to achieve meaningful learning on the students behalf. Finally, after applying the educational product and analyzing the results obtained, we found, through the resolutions developed by the students, that they showed interest and skills (mathematical and conceptual) necessary for understanding the contents of MCP, a factor that contributes, significantly, for the scientific formation of the students.